2012
DOI: 10.1590/s0102-09352012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of Santa Inês ewes submitted to short-term treatment with re-used progesterone devices

Abstract: The aim of this study was to verify the efficacy of reusing intravaginal progesterone (P4) devices on the reproductive parameters in Santa Inês ewes. Females received intravaginal P4 devices for their first, second or third use for five days plus 300 IU eCG IM and 5mg dinoprost laterovulvar 24h before device removal. Blood was collected at different moments. Transrectal ultrasonography was performed from device removal to ovulation. Part of the ewes were submitted to artificial insemination by laparoscopy (IAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 21 publications
5
15
1
10
Order By: Relevance
“…Thus, according to the data obtained in the present experiment, where the beginning of the LH peak occurred 26‐37 hr (Table ) after CIDR removal, and taking into account that frozen semen remains viable for only 6 hr in the reproductive tract, we can affirm that the optimal time for AI is approximately 50 hr because the ewes in this study ovulated at 60 (G‐6 IN), 49 (G‐12 IN), 51 (G‐6 OUT), and 52 hr (G‐12 OUT) after removal of the CIDR, 52 hr on average. In another Brazilian study, Santa Inês ewes ovulated on average 55 hr after CIDR removal, reinforcing the findings of the present study (Pinna et al., ).…”
Section: Resultssupporting
confidence: 89%
“…Thus, according to the data obtained in the present experiment, where the beginning of the LH peak occurred 26‐37 hr (Table ) after CIDR removal, and taking into account that frozen semen remains viable for only 6 hr in the reproductive tract, we can affirm that the optimal time for AI is approximately 50 hr because the ewes in this study ovulated at 60 (G‐6 IN), 49 (G‐12 IN), 51 (G‐6 OUT), and 52 hr (G‐12 OUT) after removal of the CIDR, 52 hr on average. In another Brazilian study, Santa Inês ewes ovulated on average 55 hr after CIDR removal, reinforcing the findings of the present study (Pinna et al., ).…”
Section: Resultssupporting
confidence: 89%
“…The number of ovulations per ewe, the average follicular diameter and interval to ovulation did not differ between groups and were similar to other studies (Pinna et al, 2012). Other studies with short progestagen protocols showed similar efficiency.…”
Section: Resultssupporting
confidence: 88%
“…This decrease in pregnancy rate may be related to the dominant follicle lifespan prolongation provoked by low P4 concentrations during treatment (Rubianes, Castro, &1996 & Carbajal, ; Viñoles et al, ). Additionally, Vilariño et al () and Pinna et al () showed that the use of new or once‐used devices was as effective as the use of new devices to synchronize oestrus and ovulation, with similar reproductive parameters observed when the short‐term protocol was used. Other studies have also demonstrated the possibility of reusing these devices in shorter treatment protocols (Cox et al, ; Nogueira et al, ; Vilariño et al, ; Vilariño, Rubianes, Lier, & Menchaca, ).…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, the efficacy of short‐term using of CIDRs which previously used for different durations (6, 12, 18, 24 or 30 days) on reproductive performance and hormone profiles has not been widely investigated in sheep (Pinna et al, ; Ungerfeld, ; Ungerfeld et al, ; Vilariño et al, ). Additionally, the economic evaluation of using previously used CIDRs for oestrus synchronization in sheep has never been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation